Targets Fishing and Identification of Calenduloside E as Hsp90AB1: Design, Synthesis, and Evaluation of Clickable Activity-Based Probe - Wang, Shan; Tian, Yu; Zhang, Jing-Yi; Xu, Hui-Bo; Zhou, Ping; Wang, Min; Lu, Sen-Bao; Luo, Yun; Wang, Min; Sun, Gui-Bo; Xu, Xu-Dong; Sun, Xiao-Bo (Frontiers in Pharmacology, 2018)
Calenduloside E (CE), a natural triterpenoid compound isolated from Aralia elata, can protect against ox-LDL-induced human umbilical vein endothelial cell (HUVEC) injury in our previous reports. However, the exact targets and mechanisms of CE remain elusive. For the sake of resolving this question, we designed and synthesized a clickable activity-based probe (CE-P), which could be utilized to fish the functional targets in HUVECs using a gel-based strategy. Based on the previous studies of the structure-activity relationship (SAR), we introduced an alkyne moiety at the C-28 carboxylic group of CE, which kept the protective and anti-apoptosis activity. Via proteomic approach, one of the potential proteins bound to CE-P was identified as Hsp90AB1, and further verification was performed by pure recombinant Hsp90AB1 and competitive assay. These results demonstrated that CE could bind to Hsp90AB1. We also found that CE could reverse the Hsp90AB1 decrease after ox-LDL treatment. To make our results more convincing, we performed SPR analysis and the affinity kinetic assay showed that CE/CE-P could bind to Hsp90AB1 in a dose-dependent manner. Taken together, our research showed CE could probably bind to Hsp90AB1 to protect the cell injury, which might provide the basis for the further exploration of its cardiovascular protective mechanisms. For the sake of resolving this question, we designed and synthesized a clickable activity-based probe (CE-P), which could be utilized to fish the functional targets in HUVECs using a gel-based strategy.